High‐Performance, High‐Index‐Contrast Chalcogenide Glass Photonics on Silicon and Unconventional Non‐planar Substrates. Issue 5 (14th February 2014) - Zou, Yi; Zhang, Danning; Lin, Hongtao; Li, Lan; Moreel, Loise; Zhou, Jie; Du, Qingyang; Ogbuu, Okechukwu; Danto, Sylvain; Musgraves, J. David; Richardson, Kathleen; Dobson, Kevin D.; et al.
<x xml:space="preserve">Abstract</x> This paper reports a versatile technique for the fabrication of high‐index‐contrast photonic structures on both silicon and plastic substrates. The fabrication technique combines low‐temperature chalcogenide glass film deposition and resist‐free single‐step thermal nanoimprint to process low‐loss, sub‐micron single‐mode waveguides with a smooth surface finish using simple contact photolithography. Using this approach, the first chalcogenide glass microring resonators are fabricated by thermal nanoimprinting. The devices exhibit an ultra‐high quality factor of 4 × 105 near 1550 nm wavelengths, which represents the highest value reported in chalcogenide glass microring resonators. Furthermore, sub‐micrometer nanoimprinting of chalcogenide glass films on non‐planar plastic substrates is demonstrated, which establishes the method as a facile route for the monolithic fabrication of high‐index‐contrast devices on a wide array of unconventional substrates.